Economic evaluation of a computed tomography directed referral strategy for chronic rhinosinusitis. (29th March 2016) - Kilty, S.J.; Leung, R.; Rudmik, L.
Abstract : Background: Chronic rhinosinusitis (CRS) is a prevalent chronic inflammatory disease. The basis of a clinical diagnosis of CRS for primary care physicians (PCPs) is based upon the recognition of a symptom constellation that manifests with the disease. However, because the symptomatology of CRS may overlap with other diagnoses, the referral of patient to the most appropriate specialist may not always occur, leading to further delays in evaluation and treatment. Methods: Given the emphasis on improving the value of health care in Canada, a decision tree model was designed to evaluate whether an upfront computed tomography (CT) scan of the paranasal sinuses ordered by the PCP for a suspected case of CRS would be more cost‐effective when compared to symptom‐based specialist referral practice. Results: The CT‐based strategy resulted in the patient arriving at the most appropriate specialist 95% (±5%) of the time while the symptom‐based referral strategy resulted in the patient arriving at the correct specialist 77% (±18%) of the time. The incremental cost effectiveness ratio (ICER) for the CT‐based strategy was $1522 per patient arriving at the correct specialist. Conclusion: These results suggest that PCPs can improve the effectiveness of their referrals for CRS by utilising an upfront CT referral strategy. However, it would create an additional cost of approximately $1500 per patient referred. Given these findings, the potential clinical benefits of using an upfront CT scan in the Canadian primary care setting should be further studied to determine the value of the additional money spent to improve the effectiveness of CRS referral.